MENGEVALUASI KEBERHASILAN SUPERVISI PEMBELAJARAN - Fathurrahman Fathurrahman (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
Success of supervision should contribute to the achievement of learning and education objectives. Therefore the success of supervised learning to be seen with the evaluation of the learning supervision of three main components; supervisor and their programs, teacher supervised, and students after the teachers received treatment of supervision. Principals as supervisors play a role in carrying out supervisory functions, the approach chosen, implementasion and providing advice to teachers who supervised learning process to carry out repairs in the future. Teachers as learning leaders who receive treatment of supervision to evaluate the new understanding, increase competence, and their respond to the advice given by the supervisor to make improvements in the learning process. Then evaluation is conducted to students after teacher got the supervision to know the success rate of learning of the subject matter that has been received. Furthermore the learning supervision will get the impact to the school’s human resources development.